(untitled) (Journal of Educational Sciences, 2020)
His paper explores ethical and methodological challenges experienced by educational researchers in undertaking fieldwork in Central Asia, particularly Kazakhstan, Kyrgyzstan and Tajikistan. Based on empirical data generated by interviews with international and local researchers, the identified challenges were categorized into six groups: underdeveloped research culture, limited understanding of research ethics, unreliable secondary data, difficulties in gaining access to and selecting participants, challenges in building trust and ensuring confidentiality, language barriers, and dilemmas in disseminating research results. Although these challenges can be blamed on political, social and cultural context of Central Asian countries, some of them were caused by the subjective factors. Overall, the paper contributes to the debates of ethical and methodological challenges encountered by researchers in a non-Western con- text and, as such, can be useful to researchers, university administration and policy makers of the region. 21 interviews with foreign and local researchers were conducted. The authors offered recommendations for the development of educational researches in Central Asia. Among them: they suggested to take into account the labor costs of lecturers for research activities, improve the quality of scientific and meth- odological training of young researchers, develop pluralism of scientific methodology, use quantitative, qualitative and mixed research methods; develop ethic boards and their procedures. Key words: educational research, research in Central Asia, research culture, research ethics.